2017
DOI: 10.3390/su9061005
|View full text |Cite
|
Sign up to set email alerts
|

Can Facebook Aid Sustainability? An Investigation of Empathy Expression within the Humans of New York Blog

Abstract: This qualitative study offers a novel exploration of the links between social media, virtual intergroup contact, and empathy by examining how empathy is expressed through interactions on a popular social media blog. Global leaders are encouraging individuals to engage in behaviors and support policies that provide basic social foundations. It is difficult to motivate people to undertake such actions. However, research shows that empathy intensifies motivation to help others. It can cause individuals to see the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
(47 reference statements)
0
3
0
1
Order By: Relevance
“…An exploratory study by Wheeler and Quinn (2017) found evidence for empathetic expressions in audience responses to a small sample of HONY posts. They suggested that HONY "provides a distinct opportunity to examine empathetic expression and virtual intergroup contact as the HONY community is a rare social media-based vehicle for connecting with strangers on an unprecedented worldwide scale" (Wheeler and Quinn 2017). This study aimed to build on that, to determine whether HONY might promote prosocial reactions without provoking compassion fatigue.…”
Section: Humans Of New York the Contact Hypothesis And Empathymentioning
confidence: 99%
See 2 more Smart Citations
“…An exploratory study by Wheeler and Quinn (2017) found evidence for empathetic expressions in audience responses to a small sample of HONY posts. They suggested that HONY "provides a distinct opportunity to examine empathetic expression and virtual intergroup contact as the HONY community is a rare social media-based vehicle for connecting with strangers on an unprecedented worldwide scale" (Wheeler and Quinn 2017). This study aimed to build on that, to determine whether HONY might promote prosocial reactions without provoking compassion fatigue.…”
Section: Humans Of New York the Contact Hypothesis And Empathymentioning
confidence: 99%
“…Previous research about the HONY feed has suggested that the creator changed his approach over the first few years of the project, evolving to use captions that feature the subject speaking directly to the audience, an approach in line with the public service value of journalism (Roberts 2019). An analysis by Wheeler and Quinn (2017) found evidence for empathy in a sample of comments on HONY posts, suggesting that members of the HONY audience expressed empathy for the people featured in the feed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desde la evidencia científica se puede definir un perfil de las personas con mayor empatía y comprensión de los efectos del cambio climático: son mujeres, con niveles avanzados de educación, con conexión afectiva por la naturaleza, y políticamente liberales [27][28][29] . Los análisis desde otras perspectivas como la Orientación de la Dominancia Social (ODS), en donde se define que los individuos con alta dominancia social son los que aceptan la inequidad social entre los grupos, la jerarquía entre los grupos, como algo natural y que es moralmente aceptable 30 ; así desde esta perspectiva se ha evidenciado que las personas que tienen bajos niveles de empatía y altos niveles de ODS tienen menos valores medioambientales (preservación de la naturaleza) [20][21][22] .…”
Section: Introductionunclassified